PENGARUH STORE-SPESIFIC GOALS TERHADAP UNPLANNED BUYING PADA CARREFOUR DI KOTA MOJOKERTO - UTOMO, ANDRE GUNNA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Unplanned buying is a buying activity made unplanned before or buying decision happened when the shoppers in store. Unplanned buying could increase buying numbers in store. Unplanned buying usually began with store-specific goals. To make unplanned buying on store, we need to know what makes people go to store. Store-specific goals consist of pricing, service, assortment, specific convenience, general convenience, and crowding. The purpose of this study was to determine the effect of store-specific goals on unplanned buying at Carrefour in Mojokerto. This research is the study of hypothesis testing, with members of the population of all buyers at Carrefour in Mojokerto with a total sample of 100 respondents. The sampling technique in this study used a non probability sampling with a purposive sampling method. The analysis technique used multiple linear regression analysis. The research summarize that store-specific goals which has significant effect to unplanned buying at Carrefour in Mojokerto were pricing, assortment, specific convenience , and crowding. Service and general convenience were not has significant effect at Carrefour in Mojokerto. Pricing has dominant influence on unplanned buying at Carrefour in Mojokerto.